Robotic single‐site cholecystectomy. Issue 1 (21st October 2013) - Morel, Philippe; Buchs, Nicolas C.; Iranmanesh, Pouya; Pugin, François; Buehler, Leo; Azagury, Dan E.; Jung, Minoa; Volonte, Francesco; Hagen, Monika E.
Abstract Background Minimally invasive approaches for cholecystectomy are evolving in a surge for the best possible clinical outcome for the patients. As one of the most recent developments, a robotic set of instrumentation to be used with the da Vinci Si Surgical System has been developed to overcome some of the technical challenges of manual single incision laparoscopy. Methods From February 2011 to February 2013, all consecutive robotic single site cholecystectomies (RSSC) were prospectively collected in a dedicated database. Demographic, intra‐ and postoperative data of all patients that underwent RSSC at our institution were analyzed. Data were evaluated for the overall patient cohort as well as after stratification according to patient BMI (body mass index) and surgeon's experience. Results During the study period, 82 patients underwent robotic single site cholecystectomy at our institution. The dominating preoperative diagnosis was cholelithiasis. Mean overall operative time was 91 min. Intraoperative complications occurred in 2.4% of cases. One conversion to open surgery due to the intraoperative finding of a gallbladder carcinoma was observed and two patients needed an additional laparoscopic trocar. The rate of postoperative complications was 4.9% with a mean length of stay of 2.4 days. No significant differences were observed when comparing results between robotic novices and robotic experts. Patients with higher BMI trended towards longer surgical console and overall operative time, but resulted in similar rates of conversions and complications when compared to normal weight patients. Conclusions Robotic Single‐Site cholecystectomy can be performed safely and effectively with low rates of complications and conversions in patients with differing BMI and by surgeons with varying levels of experience.